KARAKTERISTIK RUMAH TANGGA MISRIN DI DAERAH ISTIMEWA YOGYAKARTA - Faturochman Faturochman; Marcelinus Molo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
The proximate of poverty level is based on expenditure per individual member of a household. The low expenditures are primarily found among households engaged in labouring activities or in agricultural sector. The cousequences of a low expenditure or income is the inability of the household in providing appropriate needs for its members, including access to informations and schooling.An enhancement of humanresources development and promotionof equal access to the remunerative activities are among alternatives of raising the low income households.